Efficiency in the Use of Radiation and Primary Productivity on Forage Resources in Eastern Uruguay - Baeza, Santiago; Paruelo, José; Ayala, Walter (Agrociencia Uruguay, 2011)
Aboveground Net Primary Productivity (ANPP) is one of the most important ecosystem attributes, and the main control of stock density on grasslands. Traditionally it has been estimated from based on periodical biomass harvest. Spectral information allows estimating ANPP at low cost and in real time over large areas. This requires the calibration of models that relate spectral information and field estimates of ANPP, quantifying a key factor in this relationship: the conversion efficiency of radiation into biomass (Radiation Use Efficiency: RUE). In this work, we combined field ANPP estimates with data from satellite imagery and weather stations to estimate EUR and generate models to estimate ANPP in real time in natural grasslands with and without legumes overseeding, of the «Sierras y Lomadas del Este» region. RUE was 0.24 g MS/MJ for natural grassland, while sowed grassland EUR was approximately twice, depending on the system analyzed. ANPP models explained 70 and 58% of the variance of the data (p <0.001), with prediction r2 of 0,67 and 0.55 (p <0.001), to natural grasslands with and without legumes overseeding, respectively.